ANALISIS STRATEGI PEMBENTUKAN KARAKTER RASA INGIN TAHU SISWA SEKOLAH DASAR OLEH GURU SDN 192 PEKANBARU - Maharani Suci Falaah; Ilham Muhjir Revandi; Cindy Fitri Ramadhani; Mahmud Alpusari (FKIP Universitas Wiraraja, 2026)
This study aims to analyze the strategies used by elementary school teachers in developing students' curiosity character. The research employed a descriptive qualitative method, with data collected through in-depth interviews with four elementary school teachers. The findings reveal that teachers can foster curiosity in students through various strategies, such as creating an interactive classroom environment, applying project-based learning methods, assigning exploratory tasks, posing open-ended questions, and utilizing technology and educational videos. Several challenges faced by teachers include limited time to explore topics in depth, differences in students’ interests and abilities, lack of parental support, and limited access to technology at students’ homes. The study also found a positive correlation between students' curiosity and their academic performance. Students with high levels of curiosity tend to be more active in seeking information, gain a deeper understanding of the material, and demonstrate better learning outcomes. This study is expected to contribute to the development of effective and relevant teaching strategies for character education in elementary schools.